Spin in Particle Physics - Leader, Elliot (Cambridge University Press, 2001)
Motivated by dramatic developments in the field, this book provides a thorough introduction to spin and its role in elementary particle physics. Starting with a simple pedagogical introduction to spin and its relativistic generalisation, the author avoids the obscurity and impenetrability of traditional treatments of the subject. The book surveys the main theoretical and experimental developments, as well as discussing exciting plans for the future. Emphasis is placed on the importance of spin-dependent measurements in testing QCD and the Standard Model. This book will be of value to graduate students and researchers working in all areas of quantum physics and particularly in elementary particle and high energy physics. It is suitable as a supplementary text for graduate courses in theoretical and experimental particle physics.